Cloning and Characterization of Alcohol Dehydrogenase (Adh) Promoter Region for Expression Under Submergence and Salinity Stress (Plant Tissue Culture and Biotechnology, 2014)
The characterization of promoter is important for developing stress tolerant crops as well as understanding the role of promoters in regulating gene expression. The current study was initiated with an aim to characterize the Adh promoter under salinity and submergence stress in rice calli. The upstream regions (~1kb) of the Adh gene was amplified from the genomic DNA of Arabidopsis (Columbia Ecotype). The amplified product was then cloned successively into an entry and promoter-characterization binary destination vector having the reporter gene ?-glucuronidase (GUS) by applying Gateway Technology. A positive clone was confirmed by applying PCR, restriction digestion and sequencing. The construct was then transformed into Agrobacterium tumefaciens LBA4404 strain and rice calli infected with the latter. In both salt and submergence stresses, Adh could selectively express GUS gene activity up to two-fold compared to control. Plant Tissue Cult. & Biotech. 24(1): 111-120, 2014 (June) D. O. I. http://dx.doi.org/10.3329/ptcb.v24i1.19252